Utilizing Faceapp Application as Media in Teaching Speaking (Practical Ideas and Implementation Guidelines for Speaking Class) - Jaftiyatur Rohaniyah; Samsi Rijal (English Teaching Journal : A Journal of English Literature, Language and Education, 2020)
Nowadays, Indonesia was facing Industrial revolution 4.5 and comes for 5.0. It was impacted in all of sector of education especially in teaching-learning process. From these, the stick-holder of department of institution have to fine new solution in facing this era, moreover the condition amid Covid 19 Pandemic. All teacher or even a lecturer have to find solution to renew the method in teaching. As researcher found today in utilizing FaceApp application as a media in teaching speaking skill. This Application can be implemented through practical guidelines made by research which was written in this research articles to be interesting media in teaching speaking. This media can be implemented to do students in trying to describe, discuss, identify, and explain also report about the picture they have as speaking activity in the class. Thus, from this, the researcher classified two research focuses. These are: How are the guidelines of implementing FaceApp as teaching media in speaking and how do student practice their speaking skill by using this media. The method of this research was qualitative descriptive research. Where, the researcher try to describe the practical guideline of FaceApp media in teaching speaking skill. The data of this research is students' speaking transcription gotten in the speaking class activity. While, the source of data in this research is the class activity itself which was recorded in video. In the result of this research was the researcher found ten guidelines for implementing FaceApp application as a media in teaching speaking. These ten practical guidelines can be used to run speaking class activity in describing, analyzing, identifying, discussing and group pairing discussing as speaking practice for English language skill.